A Morpho-Phonemic Analysis of the Language Variety of Porohanon Speech Community (Journal of Namibian Studies : History Politics Culture, 2023)
The phenomenon of people flocking temporarily to a new place often beset with linguistic differences. These differences vary. This type of sociolinguistic phenomenon is a universal predicament experienced by majority of people around the globe. Delving into the very lens of the social community and when one speaks, he/she cannot avoid giving his/her listeners clues about one’s origins and the sort of person he/she is. In Porohanon speech community, the locals speak varieties of words unintelligible or unknown to many. Hence, this study determined the morphophonemic variations of Porohanon speech community as to function and content words and delineated the isoglosses utilized by the locals. This study is anchored on Parker and Riley’s Theories of Language Variations, Chamber and Trudgill’s Geographical Dialect Continuum and Montgomery and Beal’s Perceptual Dialectology. Results showed that Porohanon utterances in content words greatly manifest morpho-phonemic processes while the function words show otherwise. Moreover, Porohanon isoglosses demonstrate a clear demarcation where the bulk of such words are utilized and where variations are commonly employed. It can be concluded that the language of Porohanon speech community underwent various morphological processes embodying a number of variations as reflected in the isogloss mapping. Therefore, the Porohanon speech community makes use of a language that is dynamic. It is recommended that Porohanon word transformations be studied and integrated at the foundation stage from levels 1-3 and should be integrated in the MTB-MLE curriculum. It is suggested that further studies on Porohanon language using a diatopic approach be analyzed.  A primer, which serves as the output of the study, is being carved out as a learning guide to anybody who wishes to learn the utterances of the Porohanons.